2021
DOI: 10.3389/fimmu.2021.660560
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Immunity and DNA Damage Response: New Friends and Old Foes

Abstract: The maintenance of genomic stability in multicellular organisms relies on the DNA damage response (DDR). The DDR encompasses several interconnected pathways that cooperate to ensure the repair of genomic lesions. Besides their repair functions, several DDR proteins have emerged as involved in the onset of inflammatory responses. In particular, several actors of the DDR have been reported to elicit innate immune activation upon detection of cytosolic pathological nucleic acids. Conversely, pattern recognition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 125 publications
0
26
0
Order By: Relevance
“…While the mechanisms of regulation and inhibition of cGAS have been extensively studied in humans ( Hertzog and Rehwinkel, 2020 ; Taffoni et al, 2021 ), less is known about these mechanisms in pigs and other livestock species. For instance, it is unknown whether cGAS binds directly to ASFV genomes in cytoplasmic viral factories; in the nucleus, where early genome replication occurs ( Simões et al, 2019 ); or in other subcellular compartments, where cGAS can also be detected ( de Oliveira Mann and Hopfner, 2021 ).…”
Section: Activation Of the Cgas/sting Pathway By African Swine Fever ...mentioning
confidence: 99%
“…While the mechanisms of regulation and inhibition of cGAS have been extensively studied in humans ( Hertzog and Rehwinkel, 2020 ; Taffoni et al, 2021 ), less is known about these mechanisms in pigs and other livestock species. For instance, it is unknown whether cGAS binds directly to ASFV genomes in cytoplasmic viral factories; in the nucleus, where early genome replication occurs ( Simões et al, 2019 ); or in other subcellular compartments, where cGAS can also be detected ( de Oliveira Mann and Hopfner, 2021 ).…”
Section: Activation Of the Cgas/sting Pathway By African Swine Fever ...mentioning
confidence: 99%
“…During the last decade, a series of studies have demonstrated the complex intertwined relationship between DNA repair processes and immune responses. One key signaling axis involved in this association is the type-I Interferon (IFN-I) response known to play a critical role in the antiviral response (Taffoni et al, 2021). IFN-I response is essential to induce the transcription of genes involved in DNA repair and in nucleic acid degradation.…”
Section: Fa Proteins Are Involved In Dna Repair Processesmentioning
confidence: 99%
“…IFN-I response is essential to induce the transcription of genes involved in DNA repair and in nucleic acid degradation. Therefore, in the presence of defects in DNA repair processes or nucleic acid metabolism, cellular immune receptors can be activated by self-nucleic acids (Taffoni et al, 2021). Given that new evidence suggests that loss of function of FA proteins causes IFN-I production (Bregnard et al, 2016;Reislander et al, 2019;Heijink et al, 2019), this review explores how defect in the FA pathway might contribute to the accumulation of cytosolic nucleic acids and activation of IFN-I (Figure 2).…”
Section: Fa Proteins Are Involved In Dna Repair Processesmentioning
confidence: 99%
“…Even if DNA damage does not directly kill cells, increasing evidence indicates that the accumulation of nucleic acids in the cytoplasm caused by DNA damage can also trigger an inflammatory response within the cells ( Nastasi et al, 2020 ). DNA damage-induced cytosolic nucleic acid shares common receptors (pattern recognition receptors, PRRs) and downstream effectors with those induced by viral or bacterial infections ( Takeuchi and Akira, 2010 ; Taffoni et al, 2021 ), which are summarized below ( Figure 1 ). And some agonists of these nucleic acid-sensing pathways are already in clinical trials ( Table 1 ).…”
Section: Nucleic Acid-sensing Pathways Connect Dna Damage To Innate I...mentioning
confidence: 99%